RESULTS AND COMPLICATIONS IN RESECTION OF PITUITARY TUMORS BY NASAL TRANSEPTOSPHENOIDAL ENDOSCOPY - Garavaglia, Federico Ignacio; Paoletti, Oscar; Herrera, Enrique; Pueyrredon , Francisco; Montivero , Agustín; Cabanillas , Juan; Viano, Juan Carlos (Revista Argentina de Neurocirugía, 2021)
OBJECTIVES Describe results and complications of resection of pituitary tumors by the sphenoid transept endoscopy. Analyze different variables among themselves. METHODS Descriptive, retrospective, longitudinal and observational study, n = 32. Variables related to the approach, closure of the sellar region and complications, histology, resection results and recurrence were studied. RESULTS n = 32 patients, 3 (9.38%) tumors were microadenomas and 29 macroadenomas (90.63%). CSF fistula was observed in 4 patients (12.50%). A rupture of the sellar diaphragm was observed visible during surgery in 6 patients (18.75%). It was observed that of the 16 patients (50%) in the study with visual field alteration, 100% obtained a postsurgical improvement, this being statistically significant (p <0.05). It was observed that the patients with opening of the sellar diaphragm, which were 6, presented a higher proportion of CSF fistula. Regarding the analysis of the variables resection and recurrence, it was observed that the resection was total in 23 patients (71.88%) and it was not in 9 patients (28.13%). The mean follow-up time for the 32 patients was 17.97 months (± 12.78). The mean length of stay was 8 days (± 5.58). The pathological anatomy data and the KI67 / MIB1 cell proliferation value were entered. CONCLUSION Endoscopy is an undisputed technique when treating pituitary tumors; it is a fundamental weapon as a complement to the skull base surgeon. Endoscopy is constantly advancing which is a great challenge for the next generations. Key words: Endoscopy, pituitary, sellar region, complications, results